Sedation and analgesia for procedures in the pediatric emergency room, - Carlos Eduardo Ramalho; Pedro Messeder Caldeira Bretas; Claudio Schvartsman; Amélia Gorete Reis
Abstract Objective: Children and adolescents often require sedation and analgesia in emergency situations. With the emergence of new therapeutic options, the obsolescence of others, and recent discoveries regarding already known drugs, it became necessary to review the literature in this area. Data sources: Non-systematic review in the PubMed database of studies published up to December 2016, including original articles, review articles, systematic reviews, and meta-analyses. References from textbooks, publications from regulatory agencies, and articles cited in reviews and meta-analyses through active search were also included. Data synthesis: Based on current literature, the concepts of sedation and analgesia, the necessary care with the patient before, during, and after sedoanalgesia, and indications related to the appropriate choice of drugs according to the procedure to be performed and their safety profiles are presented. Conclusions: The use of sedoanalgesia protocols in procedures in the pediatric emergency room should guide the professional in the choice of medication, the appropriate material, and in the evaluation of discharge criteria, thus assuring quality in care.